Seasonal and spatial patterns in diazotroph community composition at Station ALOHA - Turk-Kubo, Kendra A.; Henke, Britt A.; Gradoville, Mary R.; Magasin, Jonathan D.; Church, Matthew J.; Zehr, Jonathan P. (Frontiers in Marine Science, 2023)
Dinitrogen (N2) fixation is carried out by specialized microbes, called diazotrophs, and is a major source of nitrogen supporting primary production in oligotrophic oceans. One of the best-characterized diazotroph habitats is the North Pacific Subtropical Gyre (NPSG), where warm, chronically N-limited surface waters promote year-round N2 fixation. At Station ALOHA (A Long-Term Oligotrophic Habitat Assessment) in the NPSG, N2 fixation is typically ascribed to conspicuous, filamentous cyanobacterial diazotrophs (Trichodesmium and Richelia), unicellular free-living Crocosphaera, and the UCYN-A/haptophyte symbiosis, based on using microscopy and quantitative PCR (qPCR). However, the diazotroph community in this ecosystem is diverse and includes non-cyanobacterial diazotrophs (NCDs). We investigated the diversity, depth distributions, and seasonality of diazotroph communities at Stn. ALOHA using high throughput sequencing (HTS) of nifH gene fragments from samples collected throughout the euphotic zone (0-175 m) at near-monthly intervals from June 2013 to July 2016. The UCYN-A symbioses and Trichodesmium sp. consistently had the highest relative abundances and seasonal patterns that corroborated qPCR-based analyses. Other prevalent community members included a new Crocosphaera-like species, and several NCDs affiliated with γ- and δ-proteobacteria. Notably, some of the NCDs appear to be stable components of the community at Stn. ALOHA, having also been reported in prior studies. Depth and temporal patterns in microdiversity within two major diazotroph groups (Trichodesmium and UCYN-A) suggested that sub-populations are adapted to time- and depth-dependent environmental variation. A network analysis of the upper euphotic (0-75 m) HTS data identified two modules that reflect a diazotroph community structure with seasonal turnover between UCYN-A/Gamma A, and Trichodesmium/Crocosphaera. It also reveals the seasonality of several important cyanobacteria and NCDs about which little is known, including a putative δ-proteobacterial phylotype originally discovered at Stn. ALOHA. Collectively, these results underscore the importance of coupling nifH gene HTS with other molecular techniques to obtain a comprehensive view of diazotroph community composition in the marine environment and reveal several understudied diazotroph groups that may contribute to N2 fixation in the NPSG.